Attitudes of Parents Toward the Educable Mentally Retarded Greek Child as Influenced by Their Socio-Economic Status and the Sex of this Child - Stasinos, Demetrios P. (Études helléniques / Hellenic Studies, 1983)
This study evaluated the attitudes of parents toward their educable mentally retarded (EMR) Greek child as influenced by their socio-economic status and the sex of the child. It was hypothesized that attitudes of parents were: less favorable toward their EMR child as compared to those toward their normal child, more favorable toward their EMR child as compared to those toward other EMRs, and significantly related to the socio-economic status of parents and not to the sex of the EMR child. Eighty-three parents having at least one EMR child were used as the subjects of the present study. A 42-trait names scale adapted form the Gills’ Index of Adjustment and Values (1951) was used to evaluate theparent’sattitudes. The results confirmed these hypotheses except that concerning parents’ social class. Implications for EMR child’s mental hygiene and for creating more skillful parent counseling services in Greece were discussed.